Activitesnin PGRFA conservation at the Ministry of Agriculture, Sugar and Land Resettlement, Fiji - Kete, T.N.=700 1 Turagakula, A.; Guarino, L.
(Es, En, Fr)
ilus., 12 ref.
Keywords: RECURSOS GENETICOS; CONSERVACION DE LOS RECURSOS; ALIMENTACION; AGRICULTURA; ITALIA